DAYA TERIMA VARIAN RASA KOKTAIL BUAH NANAS (Ananas comosus L. Merr) DALAM MENUNJANG DIVERSIFIKASI PRODUK - Wiwik Endah Rahayu; Nurul Mukminah; Atika Romalasari (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Pineapple (Ananas comosus L.Merr) is one of prime product in Subang district. High production and low price make pineapple potential to be developed. Variations of pineapple cocktails’s flavor will provide an alternative to consumers in selecting products. The research used Complete Random Factorial Design method with 2 treatments, sugar concentration and different cocktail flavor. Sugar concentrations used were 20% (K1) and 30% (K2) of sugar while the flavor varians were original with the addition of cloves and cinnamon (R1), citrus flavor (R2) and rujak flavor (R3). Analysis conducted include measurement of pH and organoleptic test. The pH content was not significant (P> 0,05) on the treatment of sugar concentration. pH of K1 is 4,33 and K2 is 4,34 R3 gave higher pH value (P> 0,05) (5,36) than R1 (3,80) and R2 (3,69). Sugar concentration give very signifficant effect (P<0,01) on total soluble solid. Interaction between sugar concentration and flavor varians was not significant. The result of organoleptic test of respondents refer to K2R2 (sugar concentration 30% and citrus flavor).